A study on people awareness of the Tun Mustapha Gallery / Doris Mison - Mison, Doris (2009)
Purpose of this study are to determine whether local people are aware of the existence of Tun Mustapha Gallery which located at the most known building in this states, that is Sabah Foundation Building which now known as Menara Tun Mustapha. Furthermore to study on how to improve this gallery to be more attractive in the future trough the respond give n by the respondents. The result of this study will help Tun Mustapha's Gallery Management to find out and improve their promotion strategy and also the gallery so that people aware of the existence of this gallery and also make some improvement to the gallery itself.